'And all our classes turned into a flower garden again' – science education in Soviet schools in the 1920s and 1930s: the case of biology from Darwinism to Lysenkoism. Issue 1 (2nd January 2019) - Caroli, Dorena
ABSTRACT: The purpose of this article is to outline the evolution of biology education in Soviet schools in the 1920s and 1930s. After some introductory consideration of the ideological changes taking place in the field of genetics that impacted on the teaching of science and led to botany being favoured over biology in schools, the first part outlines the development of the natural sciences curriculum in the context of the Soviet reform of the school, which, after the October Revolution, abolished traditional teaching methods in favour of the active methods of American schools. The second part reconstructs the evolution of the teaching of biology through analysis of the biological station for young naturalists, 'K. A. Timiriazev', a centre created in 1919 by the famous biologist Boris V. Vsesviatskii(1887–1969) . The third part illustrates the characteristics of botany education in schools of the 1930s, with a focus on the dissemination of the new scientific anti-genetic conception (known as Lysenkoism) and teaching practices in city and rural schools after the publication of Vsesviatskii's textbook. The fourth demonstrates a progressive assimilation of the anti-genetic doctrine of Lysenkoism by teachers, with particular attention to the question of the natural sciences school curriculum and teacher training in the field of botany.